Avaliação das propriedades de argilas montmorillonitas natural e sintética pilarizadas com polihidroxicátions de alumínio - Nascimento, Joe Vítor Alves do (2018)
Clays are natural, earthy and widely available in nature. They have in their composition the clay minerals and various impurities. These impurities can interfere in their applications and the use of synthetic clay appears as a solution. In order to study the differences between synthetic and natural materials, the montmorillonite claymineral was synthesized under hydrothermal conditions, autogenic pressure, acidic and hydrofluoric medium. Both synthetic and natural clays were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), infrared spectroscopy (FTIR), 27Al nuclear magnetic resonance (27Al NMR), adsorption and desorption of N2, scanning electron microscopy (SEM) and energy dispersive (EDS). The synthetic clay presented an X-ray diffraction pattern with characteristic reflections of montmorillonite, like natural clay, with the exception of the presence of quartz in the mineralogical composition of the latter. By means of the analyzes, a greater amount of aluminum was identified for the synthetic clay, as well as a more meso-macroporosity character and compositional purity, when compared with the natural clay. The pillarization of the clays was done starting from two distinct sources of Keggin ions (as made in laboratory and aluminum chlorohydrol solution), one commercial and the other produced in the laboratory. The resulting materials were characterized by XRD, TGA, FTIR, 27Al NMR and adsorption and desorption of N2. The synthetic pillared materials presented a disorganized, but pillared structure, as verified by means of X-ray diffraction and textural analysis. The natural clay also pillared with both sources presented characteristics typical of the pillared materials. The use of aluminum chlorohydrol (ACH) as a source of Keggin ions generated materials with higher amounts of aluminum species in the interlamellar space, resulting in materials with a lower volume of micropores. The specific areas of the natural pillared materials were higher than those calculated for synthetic pillared clays due to a greater contribution of the microporosity created with the pillarization process.